Odejście „człowieka ferdydurkicznego” - Jarzębski, Jerzy (Przestrzenie Teorii, 2013)
Gombrowicz’s life can be divided into two parts. During the first period of his life, Gombrowicz is preoccupied with the “Ferdydurke Man”, i.e. a funny character who is tortured by Form, which he tries to overcome but which he finally succumbs to by falling into inauthenticity. This man, though incoherent, is understandable both for the author and the reader because he comes from the world they both live in and epitomizes their own problems, which makes readers laugh. The second period of Gombrowicz’s life begins with a scene in Venice in 1938. He meets young Italian pilots who are ready to destroy the city if Mussolini gives such an order. This is when new and “savage” young people take the place of the “Ferdydurke Man”. They are a product of their time – they do not think independently and they constitute a breeding ground for totalitarian ideologies. Gombrowicz tries to understand this generation and presents a picture of the world these young people are building for themselves in consecutive dark literary works.